Classification of fish images based on shape characteristic - Mohd Wafi Nasrudin (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2015)
This research work has been conducted to analyze and classify the types of fish image based on shape characteristic. The features of characteristic of fish image are extracted by using three Moment Invariants (MI) techniques and Fourier descriptors (FD).The types of Moment invariants are Geometric moment invariant (GMI), United moment invariant (UMI), Zernike moment invariant (ZMI). In the FD's technique, there are two edge detection have been used to create the boundary of the image, namely Robert cross detection and Sobel cross detection.